Experiences of Student Affairs Professionals in Facilitating Co-Curricular Leadership Development Programmes in South African Universities - Xaba, Gugulethu (International Journal of African Higher Education, 2021)
Despite the important role that student affairs practitioners play in supporting universities to produce well-rounded graduates, few studies have been conducted on their lived experiences. This article examines the challenges confronted by these professionals in interacting with student leaders and facilitating leadership programmes in South African universities. A qualitative methodology was adopted and semi-structured interviews were conducted with 20 student affairs practitioners responsible for facilitating student leadership development programmes. A focus group discussion was also held with six student affairs experts. The findings point to a lack of seamlessness in the structure, staffing, and operation of these programmes, as well as a lack of university support to professionalise student affairs. Furthermore, student leadership development programmes were found to lack proper theoretical grounding. Key words: Student leadership development programmes, students, student affairs professionals